Spontaneous carotid cavernous fistula presenting only with cranial nerve palsies. - Kurata, A; Takano, M; Tokiwa, K; Miyasaka, Y; Yada, K; Kan, S (American Journal of Neuroradiology, 1993)
PURPOSE To discuss the differences in angiographic findings between cases of spontaneous carotid cavernous fistula with and without the classical triad of symptoms (pulsating exophthalmos, bruit, and conjunctival chemosis).METHODS With CT, MR, and angiography, we examined 12 cases of spontaneous carotid cavernous fistula, five of whom presented only with cranial nerve palsies.RESULTS In the seven cases with the triad, the main venous drainage from the cavernous sinus was the superior ophthalmic vein. Only one or two veins drained the cavernous sinus, and cortical venous drainage was not present in any case. In contrast, all but one case with only cranial nerve palsies had at least three venous drainage routes from the cavernous sinus, including cortical venous drainage.CONCLUSION For the diagnoses of spontaneous carotid cavernous fistula, it is important to know that some patients do not show the classical triad of symptoms. In such patients, early diagnosis and treatment are particularly important because cortical venous drainage and a consequent risk of hemorrhage are frequently present.